DIGITAL GENERATION’S MOTIVATIONAL ADVANTAGES IN CREATIVE ECONOMICS OF DIGITAL ERA (International Journal of Innovative Technologies in Economy, 2021)
To produce a quality media product, professionals who can generate creative ideas and have sufficient skills, abilities, knowledge, intellectual potential and are also able to creatively and effectively implement it into a competitive product, are needed in the age of informatization and digitalization. However, due to transformation processes, including robotization of the media industry, the emergence of artificial intelligence, integration of creative industries with Internet resources, increasing not only of the number of products on the media market, but also their producers, including bloggers, YouTubers, prosumers, the competition to attract the audience’s attention is strengthening in various segments of the media. The digital generation of centenarians Z, who are now 20-25 years old, are becoming leading specialists in production processes at the media company in the era of creative economy, knowledge economy. This means that their intellectual potential must be so high that they can constantly generate new creative ideas and be ready for the constant regeneration of knowledge in order to create a competitive media product in a competitive environment. This study aims to examine digital generation’s preferences, creativity, skills, motivational advantages to determine the resourcefulness of the human factor in the production processes of media companies, in particular to improve communication between employees and create a quality competitive media product that can capitalize manufacturing processes on the basis of a properly chosen competitive strategy.